Essay Writing Module to Stimulate Students’ Critical Thinking - Niati, Batdal; Wahyuningsih, Destri; Rasyidah, Ummi; Antoni, Rivi (Universitas Pahlawan Tuanku Tambusai, 2023)
Todays, using technology in teaching English online is a must for lecturer. It can facilitate student and lecturer in interaction on the learning process and create an interactive and communicative classroom environment. Learning outcome of essay writing is students are able to write essay well. To achieve learning outcome, the lecturer must develop about teaching material. Module is the most suitable teaching material for the students. Module was also useful on online learning. The Purpose of this research was to create Module of essay writing valid, practice and effective and to gain effect of Module in stimulating students’ critical thinking. Method of this research is R and D (Research and Development); ADDIE Development; analysis, design, development, implementation and evaluation. Instruments of this research were Questionnaire and Writing Test. Data were gotten from the result of students’ and lecturer’s questionnaire response, validity test, and pre-test and posttest. Based on the result of Module validity; design, material, and language, the results showed that the Module had good validity. A pretest and posttest were given to get the result of implementation of writing Module in stimulating students’ critical thinking. The Sample Paired-t test was 11.094 t-table was 2.064. The results showed that the Module improved critical thinking and writing skills.